2019
DOI: 10.3390/rs11060607
|View full text |Cite
|
Sign up to set email alerts
|

Use of RGB Vegetation Indexes in Assessing Early Effects of Verticillium Wilt of Olive in Asymptomatic Plants in High and Low Fertility Scenarios

Abstract: Verticillium Wilt of Olive, a disease caused by the hemibiotrophic vascular fungus Verticillium dahliae Kleb. presents one of the most important constraints to olive production in the world, with an especially notable impact in Mediterranean agriculture. This study evaluates the use of RGB vegetation indexes in assessing the effects of this disease during the biotrophic phase of host-pathogen interaction, in which symptoms of wilt are not yet evident. While no differences were detected by measuring stomatal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 44 publications
3
19
0
1
Order By: Relevance
“…The use of UAV imagery is a valuable tool/methodology for identifying diseases affecting citrus plants in South Texas, as well as other citrus producing regions. Our study shows conflicting results from current studies using UAV collected images, with no correlations between plant nitrogen status and TGI [10,14,17,[30][31][32][33]. This further supports evidence that UAV-collected RGB image data is highly variable, and also could be confounded by disease status because of the lack of correlation between TGI and nitrogen status.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…The use of UAV imagery is a valuable tool/methodology for identifying diseases affecting citrus plants in South Texas, as well as other citrus producing regions. Our study shows conflicting results from current studies using UAV collected images, with no correlations between plant nitrogen status and TGI [10,14,17,[30][31][32][33]. This further supports evidence that UAV-collected RGB image data is highly variable, and also could be confounded by disease status because of the lack of correlation between TGI and nitrogen status.…”
Section: Discussionsupporting
confidence: 46%
“…Many factors have the potential to influence measured and TGI values. Many studies using TGI as an indicator of plant status focus on its correlation with chlorophyll or N content [10,14,17,26,30,31,33]. However, the relationship between pigments and TGI did not fully explain their results indicating that more factors influence TGI [31].…”
Section: Discussionmentioning
confidence: 99%
“…The spectral measurements acquired by portable instruments, called proximal sensing, are also included in this definition [83]. These methods are rapid, non-destructive, and cost-effective, enabling the user to collect data rapidly compared to the usually time-consuming diagnosis/detection by ground-based techniques [84,85]. As mentioned above, V. dahliae infects the plant through the roots and colonizes its vascular system, blocking the water flow to the aboveground organs and eventually leading to the characteristic wilting syndrome [16].…”
Section: Detecting the Pathogen: From Remote Sensingmentioning
confidence: 99%
“…Therefore, the data obtained by UAV showed that normalized olive canopy temperature, chlorophyll fluorescence, and blue/blue-green/blue-red ratios (B/BG/BR indices) were found to be the best indicators of early stage infection by the pathogen, while the Photochemical Reflectance Index (PRI), structural, chlorophyll, and carotenoid indices detected only moderate to severe V. dahliae infections [85,86]. Furthermore, a very recent study even included the use of indices derived from RGB (red-green-blue) images for the first time to assess VWO in combination with control strategies, such as the use of organic amendments [84].…”
Section: Detecting the Pathogen: From Remote Sensingmentioning
confidence: 99%
“…The digital image technology is developed and the high-resolution camera equipment is widely used, the digital imaging technology has obvious advantages of high resolution and low cost in research of plant phenotype (Chen et al, 2014;He et al, 2017). Digital color image is not only convenient to obtain (Sancho-Adamson et al, 2019), but also contains abundant information about plant morphology, structure, and color gradation (Liu et al, 2015;Grosskinsky et al, 2018;Vasseur et al, 2018), which can re ect the internal status of plants. RGB color model is the popular used color representation for digital images (Barker et al, 2016).…”
Section: Introductionmentioning
confidence: 99%